Development of Fe2O3/YSZ ceramic plates for cryogenic operation of resistive-protected gaseous detectors - Olano-Vegas, L.; Pardo, I.; Leardini, S.; Morales, M.; Carreira, A. R.; Corral, R. M.; González-Díaz, D.; Tesi, A.; Moleri, L.; Azevedo, C. D. R.; Carramate, L.; Guitián, F. (Frontiers in Detector Science and Technology, 2023)
We present a ceramic material based on hematite (Fe2O3) and zirconia stabilized with yttria at 8% molar (YSZ), that exhibits stable electrical properties with transported charge and that can be tuned to the resistivities necessary to induce spark-quenching in gaseous detectors (ρ = 10 9 -10 12 Ω•cm), from room temperature down to the liquid-vapor coexistence point of nitrogen (77 K). It, thus, allows covering the operating temperatures of most immediate interest to gaseous instrumentation. The ceramics have been produced in a region of mass concentrations far from what has been usually explored in literature: optimal characteristics are achieved for Fe2O3 concentrations of 75%wt (LAr boiling temperature), 35%wt (LXe boiling temperature), and 100%wt (room temperature). The nine-orders-of-magnitude enhancement observed for the electrical conductivity of the mixed phases relative to that of pure Fe2O3 is startling, however it can be qualitatively understood based on existing literature. Plates of 4 cm × 4 cm have been manufactured and, prior to this work, operated in-detector at the LXe boiling point (165 K), demonstrating spark-free operation. Illustrative results obtained for the first time on a spark-protected amplification structure (RP-WELL) at around the LAr boiling point (90 K) are now presented, too.